TIMELESS VIEW OF PHILIP CAREY’S EMOTIONAL ISOLATION IN WILLIAM SOMERSET MAUGHAM’S OF HUMAN BONDAGE - Adila Wandari; Dwi Aji Prajoko (Humaniora Scientia, 2021)
Emotional isolation originates from traumatic experiences in a person’s past that are hiddenfrom consciousness and may cause problems during adulthood in the form of obsessive orcompulsive behaviors. These behaviors were portrayed in Philip Carey, the main character inWilliam Somerset Maugham’s novel Of Human Bondage. The research was qualitative, and thetechnique of collecting data was ethnographic. The approaches used were the psychologicalapproach and sociological approach. This research used psychoanalysis theory: personalprinciples and defense mechanism by Sigmund Freud, which contains about the conscious andunconscious side of humans and the application in their behavioral life. Emotional isolationbehaviors portrayed in Philip Carey were a self-conscious person, an introvert, an impulsive,and an attention seeker. Philip Carey’s abnormal behaviors occurred for some reasons. First, hedid not have parents taking care of him. Second, he had to live with his cruel and abusive uncle.He also became an object of bullying because of his clubfoot. These behaviors influenced PhilipCarey’s life. At first, he became self-conscious and delusional. Next, he failed to control his mostburdensome bondage: passion. However, in the end, he finally sought freedom from everybondage.Keywords: emotional isolation, personal principle, psychoanalysis